Beyond the Numbers : Gender Quotas and Women's Political Representation in Bengkulu Indonesia - Wahyu Widiastuti; Delfan Eko Putra (Yayasan Darussalam Bengkulu, 2026)
Despite legislative gender quotas, women remain underrepresented in politics. While institutional barriers are well-documented, the impact of local gender norms on quota success remains under-researched. This qualitative case study investigates how local norms affect female political representation in Bengkulu, Indonesia, where a 30% candidate quota is mandated. Through in-depth interviews with first-time female candidates, party leaders, and political observers, alongside documentary analysis, the study shows that quotas open formal electoral pathways but fail to dismantle deep-seated patriarchal structures. Politics is still viewed as a masculine domain, and party practices continue to marginalize women, who must constantly balance campaigning with traditional societal expectations. Nonetheless, running for office empowers women by boosting self-confidence, expanding networks, and fostering leadership ambitions. Ultimately, the study argues that local gender norms actively mediate the success of formal quotas. To achieve true political equality, interventions must target both formal electoral rules and the cultural norms governing political authority.